Analysis of the Effectiveness of the Use of Tafsir in Islamic Religious Education on the Achievement of Character Education of Junior High School Students in Central Java - Mokodenseho, Sabil; Mokoagow, Hestina; Pobela, Putri Revadila; Kobandaha, Cindra Patricia; Sabir, Ranti (Eastasouth Institute, 2024)
This qualitative research delves into the effectiveness of incorporating Tafsir (interpretation and explanation of the Quranic text) into Islamic Religious Education (IRE) classes to enhance character education among junior high school students in Central Java. Through in-depth interviews and focus group discussions, the study investigates students' perceptions, teachers' experiences, challenges, and opportunities associated with Tafsir integration. Findings reveal positive attitudes among students towards Tafsir-based education, highlighting its relevance to personal and social life, enhancement of moral awareness, and promotion of critical thinking. Teachers recognize the benefits of Tafsir in deepening students' understanding of Islamic teachings but face challenges such as limited instructional time and pedagogical constraints. However, opportunities for collaboration, curriculum enhancement, and community engagement emerge, suggesting pathways for optimizing the effectiveness of Tafsir-based education. Overall, the research contributes insights into the potential of Tafsir integration in fostering character education and ethical development among junior high school students in Central Java.